Implementasi Projek Penguatan Profil Pelajar Pancasila Rahmatan lil ‘Alamin (P5RA) di MA Alkhairaat Kota Gorontalo - Fazria Handayani Matulu; Asmun W. Wantu; Zulfikar Adjie (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to examine in depth the implementation of the Pancasila Rahmatan Lil'alamin (P5RA) Student Profile Strengthening Project and its determining factors at MA Alkhairaat, Gorontalo City. The method used was a qualitative descriptive analytical approach with a case study design. Data were collected through participant observation, documentation, and in-depth interviews, then analyzed interactively through data reduction, data display, and conclusion drawing. The results indicate that P5RA implementation is carried out systematically by integrating Pancasila values and religious moderation using Project-Based Learning (PjBL) methods and religious habituation, such as congregational Dhuha prayers. Concretely, this program has proven effective in transforming students' attitudes to be more tolerant, strengthening religious character, and increasing diversity awareness through heterogeneous group work. This study's contribution confirms that the success of P5RA is largely determined by the principal's transformational leadership and differentiated learning strategies in managing differences in student characteristics. Despite obstacles in facilities and pedagogical readiness, a humanistic-religious approach is key to the sustainability of value internalization in the madrasah.